2022
DOI: 10.5343/bms.2021.0031
|View full text |Cite
|
Sign up to set email alerts
|

Western Atlantic invasion of sun corals: incongruence between morphology and genetic delimitation among morphotypes in the genus Tubastraea

Abstract: The scleractinian corals of the genus Tubastraea Lesson, 1830 are currently globally dispersed and even so still present a confused taxonomy due to the overlap of morphological characters between the species. In this study, we investigate Tubastraea species previously found in the western Atlantic, based on the molecular marker (ITS gene) and morphology, to determine the accuracy of their descriptions. We identified three morphotypes from Brazil which were genetically delimited into two species: Tubastraea coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Morphological studies demonstrated that T. coccinea has more polyps per colony area than T. aurea and Tubastraea sp. According to Bastos et al (2022) , T. coccinea presents polyps with smaller calyx diameters than the others, and its skeleton is not as robust as that of T. aurea . Morphology may explain this result because the type of dendroid growth of Tubastraea sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological studies demonstrated that T. coccinea has more polyps per colony area than T. aurea and Tubastraea sp. According to Bastos et al (2022) , T. coccinea presents polyps with smaller calyx diameters than the others, and its skeleton is not as robust as that of T. aurea . Morphology may explain this result because the type of dendroid growth of Tubastraea sp.…”
Section: Discussionmentioning
confidence: 99%
“…Fecundity rate was monitored during the same period of growth rate sampling. Colonies of three species were collected by visual differentiation mainly based on the size, distance and type of growth of the polyps, as well as the color of the tissue and tentacles, following Bastos et al (2022) . Authorization to collect biological material in Arraial do Cabo was granted by ICMBIO (SISBIO no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the eld, colonies with at least 12 polyps were selected and removed with a hammer and chisel, being individually separated in plastic bags according to two major morphotype groups (plocoid vs. dendroid). Identi cations were based on colony aspects related to budding patterns, length and width of the corallites, theca margins (dentate vs. no dentate), and the occurrence of colony anastomosis (Bastos et al 2022; S. Serra et al unpubl data). In this study, four morphotypes of Tubastraea were considered, two dendroid and two plocoid, namely: Tubastraea sp.…”
Section: Study Areamentioning
confidence: 99%